Editorial introduction: The return of sound symbolism - Zlatev, Jordan (Public Journal of Semiotics, 2013)
This special issue of The Public Journal of Semiotics presents four contributions devoted to the phenomenon of sound symbolism: the motivated, non-arbitrary relationship between sound shapes and meanings in language.